Left subclavian artery occlusion during endovascular repair of traumatic thoracic aortic injury, cohort study. (2020) - Alhaizaey, Abdullah; Aljabri, Badr; Alghamdi, Musaad; AlAhmary, Ali; karmota, Ahmad G.; Asiry, Mohammed; Al-Omran, Mohammed; Alhazmi, Barrag; Abulyazied, Ahmed; Abbass, Mustaffa; Azazy, Ahmed
Abstract: Background: Thoracic endovascular aortic repair (TEVAR) is superior to open techniques, as it is a minimally invasive procedure with low morbidity and mortality rates. The aortic isthmus is usually the rupture site in aortic thoracic injuries. Therefore, the distance from the left subclavian artery (LSA) usually allows proximal stent graft fixation. The main challenge is the intentional coverage of the LSA without revascularization, which is necessary to expand the proximal landing zone and to achieve an adequate seal. Acute arm ischemia, claudication, stroke, and/or left subclavian steal syndrome may occur during intentional occlusion of the LSA without revascularization when performing thoracic aorta lesion endovascular repair. The present study was conducted to analyze the safety of coverage of the LSA without revascularization during the endovascular treatment of traumatic thoracic aorta injuries. Methods: A retrospectively collected data set from two trauma centers in Saudi Arabia was reviewed between April 2007 and January 2018 to analyze the safety of LSA coverage during TEVAR performed for traumatic thoracic aorta transection. In this data set, 69 patients presented with descending thoracic aortic injuries. All were treated urgently with TEVAR with intentional LSA occlusion without revascularization during aortic injury endovascular repair. Those who underwent thoracotomy and pre-TEVAR patients who died were excluded from this study. Results: A total of 69 patients underwent intentional left subclavian artery (LSA) coverage without revascularization during the procedure; the primary technical success reached 94.2% for patients who underwent TEVAR for traumatic aortic transection. The clinical success rate was 98.6%. Only 1 of 69 patients with LSA coverage developed a localized ischemic stroke (1.4%). The 30-day mortality rate was 4.3% due to multiple organ failure. Conclusion: Revascularization of LSA is not mandatory with TEVAR for treating traumatic thoracic aortic injury with an inadequate proximal landing zone. Extending the landing zone to zone 2 and coverage of LSA is considered safe and non-time-consuming, especially in urgent situations. It provides better fixation and a good sealing zone. Highlights: Left subclavian artery coverage during endovascular aorta repair may be safe. Revascularization of the left subclavian artery is not mandatory in emergency cases. Low incidence of type 1 endoleaks after emergency left subclavian artery coverage.